Surgical Strategies for Divergence Excess: A Comparison of True Divergence Excess and Pseudo-Divergence Excess Cases: Poster Presentation - Case Series - Resident - Julita; Anshari, Harsya Luthfi (Majalah Oftalmologi Indonesia, 2023)
Introduction : True divergence excess (True DE) intermitent exotropia (IXT) is characterized by a greater deviation at distance than near ?10 prism diopters, while pseudo-divergence excess (Pseudo-DE) has greater deviation at distance than near but the difference becomes minimal after patching. Bilateral Lateral Recess (BLR) and Monocular Recess Resect (MRR) are commonly chosen for surgical planning. Case Illustration : Case 1, a 4-year-old female presented with squint since 1 year old. Hirschberg test showed XT 15° in near (N) and 30° in distance (D). Prism alternate cover test (PACT) result was 30 ?D (N) and 60 ?D (D). Case 2, a 4-year-old female presented with squint since 6 months old. Hirschberg test showed XT 30° (N) and 45° (D) and dominant right eye. PACT result was 70 ?D (N) and 80 ?D (D). Poor fusion was found in both cases. Both patients underwent monocular patching for 30 minutes. We diagnosed patient 1 with True DE and BLR was done, while patient 2 with IXT dominant right eye Pseudo-DE and MRR was done on the left eye. Discussion : First case was a patient with True DE who underwent 8-mm BLR, while second case was Pseudo-DE with dominant right eye who underwent monocular recess 11 mm and resection 8 mm on the left eye. Orthophoria was found after surgical correction in both cases. Conclusion : Surgery management in True DE and Pseudo-DE are challenging, especially in determining the amount of surgery dosage and it depends on surgeon's experience. Both cases achieved successful outcomes with surgical correction resulted in orthophoria.